Determination of Quercetin by HPTLC in "Calendula Officinalis" Extract - GUNO SINDHU CHAKRABORTHY; PRASHANT M GHORPADE (International Journal of Pharma and Bio Sciences, 2010)
Calendula officinalis Linn (Asteraceae), is an aromatic annual herb, which is used in Traditional System of Medicine to treat various diseases like anti-inflammatory, antitumour, antispasmodic. The reported constituents are flavonoids, glycosides and saponins. From literature it was found that the quantification work was not carried out. It is considered to contain Quercetin, confirmed by TLC and by qualitative test. Thus it was quantified using HPTLC a sensitive method for development of marker compounds. The method was carried out on precoated TLC aluminum plates with silica gel 60 GF as stationary phase using solvent system as Chloroform: Methanol (9.5: 0.5) with Rf value of 0.43. Quantitative analysis was carried out in the absorbance at 366 nm. The linearity regression for the calibration showed r = 0.6548 and 0.999 with respect to height and area in a range of 0.5-5.0 g per spot. Thus HPTLC method provides a faster and cost effective quality control for the routine analysis of Quercetin in extracts containing Calendula officinalis.